Resolution of Errors in Issuing Waqf Land Certificates in the PTSL Program (Case Study in Paninggaran Village) - Marlina Dewi Setiani; Baidhowi (Law Research Review Quarterly, 2026)
This study aims to analyze the form of errors in issuing waqf land certificates in the Complete Systematic Land Registration Program (PTSL) and examine the Legal Implications and the role of Wakif, Nadzir, KUA, and BPN in resolving these errors, with a Case study in Paninggaran Village, Pekalongan Regency. The main problem identified is the discrepancy between social facts (land that has been orally endowed and used for public interest) with administrative facts (certified land does not belong to individuals because there is no Deed of Waqf Pledge/AIW). This study uses the Empirical Juridical method with a Case Study approach. Primary data was obtained through Semi-structured interviews with Wakif, Hadir, and BPN Officers, while secondary data was obtained from laws and regulations, books, and scientific articles. Data analysis was carried out interactively with descriptive juridical techniques. The research findings indicate that errors in issuing certificates occurred because waqf was carried out orally without AIW, even though AIW is an absolute requirement based on Article 6 paragraph (2) of the Minister of ATR/BPN Regulation No. 2017. As a result, the National Land Agency (BPN) procedurally issued a land ownership certificate based on the available documents. This error created legal uncertainty and potentially transferred the waqf land to a third party. The resolution requires the preparation of an AIW by the KUA, coordination by the Nadzir, active participation of the Wakif, and verification and issuance of the certificate by the BPN. This study concludes that orderly administration from the beginning of the waqf is very important, and strengthening multistakeholder coordination can prevent similar errors in the future.